Real-time monitoring of temperature using a pulsed laser-diode-based photoacoustic system - Upputuri, Paul Kumar (2021)
Tissue local temperature information is necessary for guiding energy-based medical treatments. In cancer treatments such as thermal therapy, heating is applied to local tissue to kill the tumor cells. These techniques require a temperature monitoring device with high sensitivity. In this Letter, we demonstrate a pulsed-laser-diode-(PLD)-based photoacoustic temperature sensing (PATS) system for monitoring tissue temperature in real time. The system takes advantage of a high repetition rate (7000 Hz), a near-infrared wavelength (803 nm), and a relatively high energy 1.42 mJ/pulse laser. The system is capable of providing local temperature information at high temporal resolution of 1 ms and high sensitivity of 0.31°C. The temperature data measured with a PLD-PATS system are compared with the data provided by the commercial fiber Bragg grating sensor. The proposed system will find applications in radio-frequency ablation, photothermal therapy, and focused ultrasound, etc., used for cancer treatments.